OPTIMIZING THE INVENTORY ROUTING PROBLEM USING ADAPTIVE DIFFERENTIAL EVOLUTION ALGORITHM - Peng, Hu; Deng, Changshou; Wu, Zhijian (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
The inventory routing problem (IRP) is an NP-hard optimization problem, which integrally seeks the minimal cost of inventory and transportation in supply chain management. However, the inventory management activities and transportation activities are conflicting in most cases. Therefore, how to efficiently solve the one-to-many IRP is still a challenge and practical requirement. As a powerful and popular evolutionary algorithm, differential evolution (DE) has been successfully applied to tackle complex industry optimization problems. In this paper, a novel method for the one-to-many IRP using an adaptive DE algorithm (named aDEIRP) is proposed. In the proposed aDEIRP algorithm, the DE algorithm with the deliver routing-based solution representation is used to solve the complex one-to-many IRP problem. In addition, a modified DE with adaptive parameter control is proposed to enhance the optimization performance. Comprehensive experimental results verified the effectiveness and efficiency of the proposed method.